2002
DOI: 10.1007/s00404-002-0449-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the cell-cycle regulatory proteins (pRb, cyclin D1, p16INK4A and cdk4) in human endometrial cancer: correlation with clinicopathological features

Abstract: As a conclusion, derailments of the Rb-pathway components, cyclin D1 and cdk4 in particular, seems to participate in the endometrial cancer development in humans. Overexpression of cdk4 was related to the progression of neoplastic disease and corresponds with age of onset, suggesting a major role of altered cdk4 immunoreactivity in the progression of endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…Cyclin D1 protein is not expressed in the normal endometrium or is present only in rare cells. In contrast, immunoreactivity for cyclin D1 has been recorded in 40-69% of endometrial adenocarcinomas, [24][25][26][27][28][29] and in some studies, such an overexpression has correlated with a higher grade or stage. 24,28 Our findings are comparable as most tumors were at least focally positive and eight cases (36%) showed …”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 protein is not expressed in the normal endometrium or is present only in rare cells. In contrast, immunoreactivity for cyclin D1 has been recorded in 40-69% of endometrial adenocarcinomas, [24][25][26][27][28][29] and in some studies, such an overexpression has correlated with a higher grade or stage. 24,28 Our findings are comparable as most tumors were at least focally positive and eight cases (36%) showed …”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of cyclin D1 in endometrial cancer has been reported in previous studies. [30][31][32] Our data showed, for the first time, that the loss of DACH1 expression is a frequent event in endometrial carcinoma, which may play an important role in endometrial carcinogenesis and malignant progression. Prognosis value of DACH1 and cyclin D1 in human endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…We used HPV E6 and E7 as inhibitors of p53 and Rb function. Although genetic abnormality of the Rb locus, including loss of heterozygosity, or altered expression of Rb protein has not frequently been detected in endometrial cancer, alteration of the pathways upstream of Rb, such as aberrant expression of cyclinD1 and cdk4, has been observed in 60-70% of endometrial cancers (Niemann et al, 1997;Semczuk et al, 2004). Formation of a complex consisting of cyclinD1 and cdk4/6 induces Rb phosphorylation, resulting in activation of E2F, leading to cell cycle progression into the G1 phase.…”
Section: Creation Of Tumorigenic Endometrial Cells Y Mizumoto Et Almentioning
confidence: 99%